O PERCURSO DAS POLÍTICAS URBANA E HABITACIONAL BRASILEIRAS E SEUS "NOVOS" RUMOS - Elvira Luiza Arantes Ribeiro Mancini (Universidade Federal do Maranhão, 2008)
This research examines the development of the Urban Policy developed in Brazil in the twentieth century, as well as its ́ actions implemented in the twentieth-first century. This article also considers the political, economical and social contexts that it is taken into account in the Brazilian urbanizing process, as well as the emerging actions in order to consider areas that were occupied in an irregular and precarious way by part of the population that have no access to housing in the city areas. The research also starts to discuss the Brazilian housing policy as a reference to the analyze the study object.